2020
DOI: 10.1139/cjfr-2019-0332
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical response of the real tree root architecture under lateral load

Abstract: The impact of climate change on tree stability is often associated with a higher risk of windthrow due to higher frequency and greater magnitude of extreme climatic conditions. Higher lateral loads due to an increase in maximum wind and rainfall reduce tree anchorage because of a decrease in soil matric suction and consequently the overall strength in the system of trunk, root, and soil. This study compared the mechanical response of trees with different root architectures using static loading tests conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…Some numerical studies on root-soil interaction of trees under lateral loads (e.g. Rahardjo et al, 2009;Yang et al, 2017;Kim et al, 2020;Ramos-Rivera et al, 2020) have suggested that rooting length and depth and windward roots contributed mostly to the tree anchorage strength. However, how these findings on root-soil interaction mechanics translate to different loading conditions (groundwater, rate) is uncertain.…”
Section: Auto-generated Pdf By Review Géotechniquementioning
confidence: 99%
“…Some numerical studies on root-soil interaction of trees under lateral loads (e.g. Rahardjo et al, 2009;Yang et al, 2017;Kim et al, 2020;Ramos-Rivera et al, 2020) have suggested that rooting length and depth and windward roots contributed mostly to the tree anchorage strength. However, how these findings on root-soil interaction mechanics translate to different loading conditions (groundwater, rate) is uncertain.…”
Section: Auto-generated Pdf By Review Géotechniquementioning
confidence: 99%
“…Considering historic trees, continuous, ongoing care, and keeping them in good condition while maintaining the appropriate conservation standards is particularly important [12][13][14]. In urban areas, there are occasions in which individual trees can fail under the influence of high wind loads, thus, causing a danger to people and property [15]. A large part of this urban greenery comprises thousands of mature trees that can be found growing along roadsides, in parks, and within residential, industrial, shopping, and business districts.…”
Section: Introductionmentioning
confidence: 99%
“…b) QP2 -Quais são as principais técnicas usadas na análise e conservação da saúde das árvores e florestas urbanas, no que diz respeito ao risco de queda? i. Uma forma de avalição convencional é feita de modo subjetivo e visual por um inspetor, o que não garante que o julgamento de dois inspetores seja o mesmo para as mesmas condições(BRAZOLIN, 2009;RAMOS-RIVERA et al, 2020).…”
unclassified